Quantifying the effects of sensor coatings on body temperature measurements. Issue 1 (December 2016) - Snyder, Stephanie; Franks, Peter
Abstract Background A characterization of an organism's thermoregulatory ability informs our understanding of its physiology, ecology and behavior. Biotelemetry studies on thermoregulation increasingly rely on in situ body temperature measurements from surgically implanted data loggers. To protect the organism and the instrument, the electronics and the temperature sensor are often encased in non-conductive materials prior to insertion into the organism. These materials thermally insulate the sensor, thus potentially biasing temperature measurements to suggest a greater degree of thermoregulation than is actually the case. Results Here we present methodology to quantify and correct for the effect of sensor coatings on temperature measurements by data recording tags. We illustrate these methods using Wildlife Computer's Mk9 archival tag, field data from the peritoneal cavity of a juvenile albacore tuna (Thunnus alalunga ) and simulated data of several species of ectotherms (fish:Hemitripterus americanus, Catostomus commersoni andMaxostoma macrolepidotum ; reptiles:Macroclemys temminckii, Varanus spp.), ranging in size from 10 to 1000 g. Mk9 tags had rate constants (measures of the sensor's ability to respond to changes in temperature) of 1.79 ± 0.06 and 0.81 ± 0.07 min−1 for the external and internal sensors, respectively. The higher rate constant of the external sensor produced smaller errors than the internal sensor. Yet, both sensors produced instantaneous errors of over 1 °C for all species tested, with the exception ofT. alalunga . Conclusions The effect of sensor coatings on body temperature measurements is shown to depend on the relative values of the sensor's and the organism's rate constant and the rate of change of environmental temperature. If the sensor's rate constant is lower than that of the organism, the temperature measurements will reflect the thermal properties of the sensor rather than the organism.